Enhancing benefit finding and psychological well-being in depression care: a quasi-experimental study of group psychoeducation in Chinese adults - Lu, Xin; Xiao, Yu (Frontiers in Psychology, 2025)
BackgroundMajor depressive disorder (MDD) is a leading cause of disability globally and is often accompanied by emotional and cognitive impairments that limit individuals’ ability to perceive positive aspects of life. Within the framework of health psychology and the biopsychosocial model, meaning-based interventions such as group psychoeducation may help enhance protective psychological resources like benefit finding and overall well-being. This study evaluated the effectiveness of a structured psychoeducational group intervention in improving benefit finding, psychological well-being, and depressive symptoms among Chinese adults with MDD in a real-world clinical context.MethodsA quasi-experimental pre-test post-test design with a control group was used. A total of 114 adults diagnosed with MDD were allocated to either an intervention groups (n = 57) or a control groups (n = 57). The intervention group participated in 8 weekly sessions, each lasting 90 min. Outcome measures included the Benefit Finding Questionnaire (BFQ), the Reiff Psychological Well-being Scale, and the Beck Depression Inventory-II (BDI-II). Data were analyzed using paired and independent t-test along with analysis of covariance (ANCOVA).ResultsThe intervention group showed significant increase in benefit finding, with mean scores rising from 57.12 ± 9.48 at pre-test to 83.33 ± 9.19 at post-test (t = 16.41, p < 0.001). No significant change was observed in the control group (pre-test: 56.39 ± 10.11; post-test: 56.17 ± 9.59 post-test; t = 0.15, p = 0.413). ANCOVA controlling for pre-test scores confirmed that post-test benefit finding scores were significantly higher in the intervention group compared to the control group (F = 28.12, p < 0.001) with a medium effect size (η2 = 0.31). However, there were no statistically significant improvements in psychological well-being or depression severity between groups (p > 0.05).ConclusionThis study supports the integration of health psychology principles into mental health care by demonstrating that group psychoeducational interventions can effectively enhance benefit finding in individuals with depression, especially in collectivistic cultural contexts. However, longer or more intensive interventions may be required to observe broader improvements in psychological well-being and symptom reduction.